Browserless web data extraction: challenges and opportunities - Fayzrakhmanov, R; Sallinger, E; Spencer, B; Furche, T; Gottlob, G (Association for Computing Machinery, 2018)
Most modern web scrapers use an embedded browser to render web pages and to simulate user actions. Such scrapers (or wrappers) are therefore expensive to execute, in terms of time and network traffic. In contrast, it is magnitudes more resource-efficient to use a “browserless” wrapper which directly accesses a web server through HTTP requests, and takes the desired data directly from the raw replies. However, creating and maintaining browserless wrappers of high precision requires specialists, and is prohibitively laborintensive at scale. In this paper, we demonstrate the principal feasibility of automatically translating browser-based wrappers into “browserless” wrappers. We present the first algorithm and system performing such an automated translation on suitably restricted types of web sites. This system works in the vast majority of test cases and produces very fast and extremely resource-efficient wrappers. We discuss research challenges for extending our approach to a general method applicable to a yet larger number of cases.